Analisis Pendapat Ulama’ Madura Tentang Childfree Melalui KB Terhadap Hak Reproduksi Perempuan dalam Fikih Kontemporer - Nihalun Nada (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the opinions of Madurese Ulama' regarding Childfree through Family Planning (KB), and its relevance to Women's reproductive rights in Islamic Law adapted to the conditions of society in the modern era. Therefore, this research uses a qualitative method which is studied empirically and theoretically so that it is presented in a descriptive form that is in accordance with contemporary jurisprudence. Meanwhile, the purpose of this research is to find out the opinion of Madurese ulama regarding Childfree through Family Planning, considering that one of the purposes of marriage is to have offspring, several ulama of the Syafi'ie school of thought allow 'azl and express that 'azl is an act that abandons virtue. in carrying out sexual relations, therefore, in implementing Childfree there are several reasons that are permitted and several reasons that are prohibited. However, most Madurese ulama' prohibit Childfree if they decide, not just limit or withhold having children. This research also carried out interview techniques with 10 sources, resulting in different opinions. So in this research conclusions can be drawn about the relevance of the Family Planning Program in Childfree according to the opinion of Madurese Ulama', namely by limiting children.